Time slots in Dylan’s Oeuvre - Mai, Anne-Marie (Aktualitet - Litteratur, kultur og medier, 2023)
The dimension of time is important to Dylan in his songs, his song analyses, and his painting. In Norman Raeben’s painting school, Dylan discovered that he could break up the chronology of his artwork and turn time into intervals that open the art of singing in a new way. This paper gives examples of the use of time in Dylan’s song “Red River Shore” (released 2008), in his visual art (especially in the “Corner Flat” watercolor series [2007/2013]) and in his analyses in The Philosophy of Modern Song (2022), especially that of the song “Feel So Good.” I will discuss how Dylan uses “time slots,” i.e. time intervals or time windows, in these works. Often Dylan confronts different intervals of the past, the present, and the future; decisive moments are confronted with longer intervals or time is sliced and shown as divergent images . What do the time slots in Dylan’s art open the way for? An insight into a real now, a special spiritual dimension of existence, a mood, or the experience of something eternal? The paper additionally considers these possibilities through the frame of the oxymoron as a pervasive stylistic figure in Dylan’s artistic universe Dylan scholars.